The meaning and power of negativity: Claremont studies in the philosophy of religion, conference 2017 - Dalferth, Ingolf U.; Kimball, Trevor W. (Religion in philosophy and theology, 2021)
"Negativity is not a negative phenomenon, but omnipresent in human life and thinking. Without it, contingency and otherness, subjectivity and power, transcendence and immanence in human life and culture cannot be understood. The present volume examines forms of negativity in central religious, theological, and philosophical traditions in Western, Buddhist, and Korean thought"--